The Effect of Current Ratio on Return on Assets in Manufacturing Companies Listed on the Indonesia Stock Exchange (BEI) - Rini Antika Ritonga; Taraweh Harahap; Putri Ayu Ritonga (Journal of Economy, Accounting and Management Science (JEAMS), 2024)
In the current era of globalization, competition in the business world is increasingly fierce, and only companies that have good performance or performance can survive. The large number of competitors in the same business sector gives consumers a variety of choices, so they become more selective in choosing the products they want. This situation encourages company management to continue to increase promotions and develop effective marketing strategies to achieve profits in line with company targets. One of the main goals of establishing every business entity or company is to make a profit. This research uses quantitative methods. The population consists of 178 manufacturing companies listed on the Indonesia Stock Exchange and indexed on IDX. Based on the criteria, researchers took samples from three production companies listed on the Indonesia Stock Exchange (BEI) between 2011 and 2022. These companies are PT. Indofood CBP Sukses Makmur Tbk, PT. Indofood Sukses Makmur Tbk, and PT. Sekar Bumi Tbk. The results of the Hypothesis Test showed that the t-count value of the Current Ratio (CR) variable had an effect on Return On Assets (ROA) where the t-count value was 4.885 > from t table of 2.03224 so that the research results received Ha. The results of the Determination Coefficient state that the Current Ratio (CR) variable can contribute/is able to explain the Return On Assets (ROA) variable of 41.2% (0.412x100%=41.2%) while the remaining 58.8% (100%-41, 2%=58.8%) is explained by variables outside the research model.